Nested Newmark model to calculate the post-earthquake profile of slopes - Leshchinsky, Ben A. (Engineering geology, 2018)
The Newmark sliding block approach is a common means of evaluating permanent displacements of slopes undergoing seismic loading. However, the conventional Newmark approach omits the presence of multiple shear zones or regions of dispersed shear movement. The occurrence of these shear movements within slopes can often materialize with added vertical and lateral movements above the basal failure surface typically considered in the conventional Newmark approach. This study modifies the conventional Newmark sliding block approach by discretizing a given slope into a series of nested, critical failure wedges, each with an associated yield acceleration, termed a Nested Newmark Model (NNM). Use of the NNM enables assessment of a post-earthquake slope profile within a limit equilibrium framework based on the integration of relative displacements from the toe to the crest. The results demonstrate a different response than conventional Newmark approaches. The model outputs can account for the restriction of toe movements as well as heaving and slumping behavior of the slope face and crest, respectively. Larger seismic excitation resulted in further destabilization of nested wedges near the crest. The presented approach establishes a framework that can be extended to any type of failure geometry or series of failures, including rotational geometry. These results are compared to a numerical model, which exhibit similar behavior. This framework is conceptual, but builds upon the well-accepted Newmark sliding block approach to provide an alternative means of assessing post-earthquake slope movements. •The NNM procedure demonstrates utility for assessing a slope profile subject to horizontal or vertical changes after seismic loading.•This procedure captures regions of distributed shear within a slope and enables a geometric constraint of toe movement, as one would practically expect in realistic slope failures. The resulting profiles often demonstrate bulging and subsidence at the slope toe and crest, respectively.•The NNM framework is versatile and can be modified to incorporate a range of failure mechanisms outside of translational failures.